DETERMINAN PREFERENSI MASYARAKAT DALAM BERBELANJA KE PASAR TRADISIONAL DI KOTA BANDA ACEH - Rahmad Nur Fazli; Amri Amri; Apridar Apridar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
Abstract This study aims aims to analyze people's preferences for shopping at traditional markets in Banda Aceh City. This study uses primary data with a questionnaire of 100 respondents selected by simple random sampling. Logistic regression analysis model was used to analyze people's preferences in shopping at traditional markets which consisted of age, education, and spending expenditures in traditional markets. The results showed that the variables of age and spending on shopping did not have a significant relationship with people's preferences in shopping at traditional markets, while the education variable had a significant effect. Education has a significant effect, which means that every time there is an increase in education, people's desire to shop at traditional markets increases. It is hoped that the Banda Aceh City Government can organize, improve cleanliness and safety, so that consumers who shop at traditional markets can increase.Keywords: Preference, Age, Education, Spending in the Market Traditional.